The influence of social media on social interactions among students - Anna Yohanna (Universitas Airlangga, 2020)
Nowadays, students cannot be separated from social media. Every student can have many accounts of social media. Social media itself is one of the students' primary needs, but social media has a significant impact. The purpose of this study is that researchers want to see the positive and negative impacts of social media on the social interactions of its users. Researchers used a qualitative type with a purposive method. Researchers conducted interviews with fourteen students of the Faculty of Social and Political Sciences, Universitas Airlangga. This study indicates that students' social media has positive and negative impacts on students' social interactions with their environment. One of the positive effects of social media is that students get the latest information more easily. Meanwhile, one of the negative impacts is that students become addicted to using social media to not interact with their environment. So, social media positively and negatively influences student interactions at the Faculty of Social and Political Sciences, Universitas Airlangga.